Management of long‐term therapy with biological drugs in psoriatic patients with latent tuberculosis infection in real life setting. Issue 5 (26th May 2017) - Conti, Andrea; Piaserico, Stefano; Gisondi, Paolo; Odorici, Giulia; Galdo, Giovanna; Lasagni, Claudia; Pellacani, Giovanni
Abstract: Psoriatic patients with latent tuberculosis infection (LTBI) need a prophylaxis before starting a treatment with biological drugs. The aim of this study is to investigate the safety and efficacy of prophylaxis of LTBI in psoriatic patients receiving long‐term biological drugs. The study included 56 patients (42 male and 14 female) affected by moderate‐to‐severe psoriasis (mean PASI: 12.8 ± 6.9 SD ) treated with anti‐TNF‐α and/or anti IL 12, 23 and/or anti‐CD11 drugs with a diagnosis of LTBI. LTBI diagnosis was based on tuberculin skin test and/or QuantiFERON TB Gold test positivity and chest X‐ray suggestive, without clinical, or microbiological evidence of active disease. All patients received prophylactic therapy for 9 months with isoniazid (INH) 300 mg/day, starting 3 weeks before the beginning of biological treatment. Fifty‐four patients completed prophylaxis with INH without any adverse events or intolerance; they continue the biological treatment without appearance of active tuberculosis. One patient developed tuberculosis pleurisy in course of treatment with etanercept. The infection has been treated and after a stable remission, treatment was restarted without tuberculosis reactivation. In this retrospective analysis, the prophylaxis of LTBI whit INH was effective and safe in longer follow‐up period.